Jokowi’s Political Communication: Utilizing Social Media in Winning Gibran as Vice President of Indonesia - Sutrisno, Sutrisno; Tunaerah, Linda (Communicatus: Jurnal Ilmu komunikasi, 2024)
In the post-Reformasi era, the political dynamic of Indonesia cannot be separated from the role of elites entrenched in various government lines. The 2024 presidential and vice presidential elections also involved political elites, including President Jokowi, especially in winning the eldest son, Gibran. As President, Jokowi has various accesses to socialize with the Prabowo-Gibran work program, which is considered a symbol of the continuity of Jokowi’s program. Using qualitative methods and Roland Barthes’ semiotic theory, this article will analyze the myths in Jokowi’s political communication on social media related to the nomination of Gibran Rakabuming Raka as the 2024 Vice Presidential Candidate. This article produces three main points: denotation, connotation, and myth, and shows Jokowi’s political communication that reflects democracy and neutrality. In addition, the obstacles faced are often transformed into narratives that strengthen his leadership image. This study suggests enhancing the narrative of meritocracy and democracy, transparency in the political process, consistency in national symbols, focus on public issues, and strengthening the image of independent and progressive leadership. This research is expected to provide new insights for political practitioners and researchers in understanding the dynamics of contemporary politics in Indonesia.